Trade with Environmental Goods – A Case of Indonesia - Skoropup, Artem (2024)
Environmental Goods is a term describing the commoditiesthat are beneficial for the environment in several ways: these commodities are used to mitigate the environmental harm, monitor and measure the environmental pollution and commodities used for construction of renewable energy powerplants. The aim of the thesis is to determine, whether the stricter environmental policies will have an impact of trade volumes of Environmental Goods. Indonesia, developing economy in Southeast Asia, has been making many steps in the direction. towards transitioning to the green economy. It lacks behind developed countries in terms of strictness of environmental protection, but is making big steps towards improvement. Moreover, Indonesia has a great potential in terms of development of renewable energy powerplants making it a potential market for environmental goods. The research concluded negative impacts of stricter environmental policies on Resources management group of Environmental Goods, which should rise concerns for Indonesian policymakers.